The prognostic value of abnormal coagulation times in dogs that are at the risk of developing sepsis - Rodrigues, L (2018)
Introduction: Sepsis is a hard to define syndrome associated with a deleterious systemic inflammatory response that ultimately leads to coagulopathy, organ dysfunction, and death. The primary aim of this prospective study was to evaluate if coagulation times can be predictive of disease severity and outcome in patients at risk of developing sepsis.A secondary objective was to correlate activated partial thromboplastin time (aPTT) and prothrombin time (PT) with the quick sequential organ failure assessment (qSOFA) scoring system at the moment of admission to the intensive care unit (ICU) and evaluate their combined prognostic value. The main hypothesis of the study was: Are aPTT and PT correlated with disease severity and outcome, when associated with the qSOFA score, at the moment of admission to the ICU? Methods: A total of 43 dogs were prospectively enrolled in the study between September 2016 and March 2017. Patients that were hemodynamically altered with clinical signs of coagulopathy, infection, shock, or SIRS were included, as well as those affected by polytrauma, organ dysfunction, or neoplasia, upon presentation. These patients had at least one of these clinical signs but some had more than one. Regarding the presence of coagulopathies, all alterations in coagulation times were included. All these patients were susceptible to subclinical infections and bacterial translocation, therefore being at risk of developing sepsis. Coagulation testing and qSOFA scoring were performed at the time of admission to the ICU and were statistically analyzed using tests such as Chi-square tests, T-tests, ANOVA, HSD tests, and Pearson correlation coefficient tests. Other variables such as signalment, diagnosis, duration of hospitalization and post-discharge treatment and outcome were also recorded and analyzed. Results: Mortality rate was 34.9%. Mortality increased with the number of qSOFA points (0 points: 10%; 1 point: 30.8%; 2 points: 47.1%; 3 points: 66.7%). The aPTT was significantly higher (p = 0.029) in patients with a qSOFA score of 2 points in comparison to those with 1 point. A positive correlation was found between aPTT and PT (r = 0.406, n = 43, p = 0.005). Mean values for aPTT and PT were similar between surviving and non-surviving patients. Ten out of 15 patients (66.7%) that died did so between the first and fifth day of treatment, and 3 of the remaining 5 deaths (60%) were caused by neoplastic disease. Causes of dead included gastrointestinal disease, infectious disease,urinary tract disease, trauma, autoimmune disease, neurological disorder and neoplasia. Conclusions: The results of this study suggest the existence of hemostatic dysfunction amongst patients with a qSOFA score of 2 points. In isolation, however, prolonged coagulation times at ICU admission were not predictive of outcome.